Moving the Static Spaces by Using Contemporary Technical Treatments (Journal of the College of Basic Education, 2019)
The present research summarizes the importance of using modern technical processors in basic building materials such as concrete bricks, glass and other materials as well as finishing materials because of their ability to change the state of the interior space as it is a source of inspiration for the designer as it changed the properties of such materials such as its ability to liquefy and withstand high temperatures And dimmability and increase its intensity on the absorption of heat and reduce the noise and change the characteristics of some materials from very harsh to more compatible materials and ease of installation to be more suitable for the function of internal space as well as the achievement of aesthetic aspects where the researcher reached results in the analysis of the sample Is the lack of internal spaces to use contemporary materials in the construction of construction and the termination of internal spaces, which led to a major failure to achieve the functional aspect of visual comfort, which is one of the most important elements of the success of public library spaces..